Bystander Host Cell Killing Effects of Clostridium perfringens Enterotoxin - Archana Shrestha (American Society for Microbiology, 2016)
ABSTRACT Clostridium perfringens enterotoxin (CPE) binds to claudin receptors, e.g., claudin-4, and then forms a pore that triggers cell death. Pure cultures of host cells that do not express claudin receptors, e.g., fibroblasts, are unaffected by pathophysiologically relevant CPE concentrations in vitro. However, both CPE-insensitive and CPE-sensitive host cells are present in vivo. Therefore, this study tested whether CPE treatment might affect fibroblasts when cocultured with CPE-sensitive claudin-4 fibroblast transfectants or Caco-2 cells. Under these conditions, immunofluorescence microscopy detected increased death of fibroblasts. This cytotoxic effect involved release of a toxic factor from the dying CPE-sensitive cells, since it could be reproduced using culture supernatants from CPE-treated sensitive cells. Supernatants from CPE-treated sensitive cells, particularly Caco-2 cells, were found to contain high levels of membrane vesicles, often containing a CPE species. However, most cytotoxic activity remained in those supernatants even after membrane vesicle depletion, and CPE was not detected in fibroblasts treated with supernatants from CPE-treated sensitive cells. Instead, characterization studies suggest that a major cytotoxic factor present in supernatants from CPE-treated sensitive cells may be a 10- to 30-kDa host serine protease or require the action of that host serine protease. Induction of caspase-3-mediated apoptosis was found to be important for triggering release of the cytotoxic factor(s) from CPE-treated sensitive host cells. Furthermore, the cytotoxic factor(s) in these supernatants was shown to induce a caspase-3-mediated killing of fibroblasts. This bystander killing effect due to release of cytotoxic factors from CPE-treated sensitive cells could contribute to CPE-mediated disease. IMPORTANCE In susceptible host cells, Clostridium perfringens enterotoxin (CPE) binds to claudin receptors and then forms pores that result in cell death. Using cocultures of CPE receptor-expressing sensitive cells mixed with CPE-insensitive cells lacking receptors for this toxin, the current study determined that CPE-treated sensitive cells release soluble cytotoxic factors, one of which may be a 10- to 30-kDa serine protease, to cause apoptotic death of cells that are themselves CPE insensitive. These findings suggest a novel bystander killing mechanism by which a pore-forming toxin may extend its damage to affect cells not directly responsive to that toxin. If confirmed to occur in vivo by future studies, this bystander killing effect may have significance during CPE-mediated disease and could impact the translational use of CPE for purposes such as cancer therapy.